Endoscopic Findings of Small-Bowel Lesions in Familial Amyloid Polyneuropathy: A Case Report. Issue 11 (March 2016) - Asakura, Kensuke; Yanai, Shunichi; Nakamura, Shotaro; Kawaski1, Keisuke; Eizuka, Makoto; Ishida, Kazuyuki; Sugai, Tamotsu; Ueda, Mitsuharu; Yamashita, Taro; Ando, Yukio; Matsumoto, Takayuki
Abstract : Abstract: Familial amyloid polyneuropathy (FAP) is an autosomal dominant disease associated with the mutations in the transthyretin gene. To date, the endoscopic findings of the small-bowel lesions of FAP have never been described. We report a rare case of FAP with gastrointestinal involvement. A 71-year-old woman complaining of refractory diarrhea for 1 year was referred to our institution. She had sensory disturbance, movement disorder due to muscle weakness, and autonomic nervous system disorders including orthostatic hypotension and dysuria. Her eldest sister had cardiac amyloidosis. Small-bowel radiography and retrograde double-balloon endoscopy (DBE) revealed that fine granular protrusions were diffusely observed both in the jejunum and ileum. Histologic examination of the biopsy specimens obtained from the small bowel revealed perivascular amyloid deposits mainly in the muscularis mucosae and submucosa, which were immunoreactive with transthyretin antibodies. Analysis of the genomic DNA showed a heterozygous Gly47Val mutation in the transthyretin gene. Thus a diagnosis of FAP was established. Diffuse fine granular protrusions in the jejunum and the ileum visualized by small-bowel radiography and DBE may be characteristic of FAP. Multiple biopsies from the gastrointestinal mucosa are recommended for the definitive histologic diagnosis of FAP.